2012
DOI: 10.5039/agraria.v7i4a2110
|View full text |Cite
|
Sign up to set email alerts
|

Resposta de cultivares de trigo ao nitrogênio com e sem tratamento fúngico

Abstract: A aplicação de fungicida pode garantir maior resposta à adubação nitrogenada, visto que a aplicação de doses mais elevadas de N podem propiciar melhores condições para o desenvolvimento de algumas doenças. O objetivo deste trabalho foi avaliar os efeitos de diferentes doses de N e da aplicação de fungicida em caráter preventivo na produtividade de dois cultivares de trigo, irrigado em condições de cerrado. O experimento foi realizado em Selvíria, MS, em um Latossolo Vermelho Distrófico. Os tratamentos foram ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Theago et al (2014) obtained a quadratic response of the N level on plant height, with a maximum point at 148 kg N ha -1 . In contrast, Prando et al (2013) and Teixeira Filho et al (2012) showed that N topdressing did not influence plant height. The different responses of cultivars in plant height, depending on the application of the plant growth regulator, are related to the recommended level of trinexapac-ethyl (100 to 125 g i.a.…”
Section: Cultivarsmentioning
confidence: 76%
See 2 more Smart Citations
“…Theago et al (2014) obtained a quadratic response of the N level on plant height, with a maximum point at 148 kg N ha -1 . In contrast, Prando et al (2013) and Teixeira Filho et al (2012) showed that N topdressing did not influence plant height. The different responses of cultivars in plant height, depending on the application of the plant growth regulator, are related to the recommended level of trinexapac-ethyl (100 to 125 g i.a.…”
Section: Cultivarsmentioning
confidence: 76%
“…Theago et al (2014) obtained a quadratic response of the N level on plant height, with a maximum point at 148 kg N ha -1 . In contrast, Prando et al (2013) and Teixeira Filho et al (2012) showed that N topdressing did not influence plant height. According to Marschner (1995), the application of high levels of N in cereals increases the production of phytohormones, plant growth, and development promoters responsible for the processes of cell division and expansion, increasing stem elongation and, consequently, plant height.…”
Section: Cultivarsmentioning
confidence: 79%
See 1 more Smart Citation
“…Wheat (Triticum aestivum L.) is an annual cycle plant and a type of cool-season cereal. Wheat has great economic importance and large grain yield capacity (Teixeira Filho et al, 2010, 2012Marini et al, 2011;Theago et al, 2014). This cereal occupies over 17% of cultivable land in the world and represents approximately 30% of world grain production.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat (Triticum aestivum L.) is an annual cycle plant, considered among the cool season cereal, one that has greater economic importance, with large grain yield capacity (Teixeira Filho et al, 2010;Marini et al, 2011;Teixeira Filho et al, 2012Theago et al, 2014). The cereal occupies over 17% of cultivable land in the world and represents approximately 30% of world grain production.…”
Section: Introductionmentioning
confidence: 99%